Rethinking Lagging Regions : Using Cohesion Policy to Deliver on the Potential of Europe's Regions - Farole, Thomas (World Bank, Washington, DC, 2018)
As the World Bank’s 2012 Golden Growth report emphasized, the European Union, since its founding, has been a ‘convergence machine,’ generating wealth and a higher quality of life for the poorest in the 28 EU member states. More recently, the Growing United report highlighted that while the convergence machine still works, it is not working for everyone. And among the fault lines emerging in the convergence machine, regional inequality represents a potent threat to Europe’s economic well-being, and to its social and political cohesion. In this context, Rethinking Lagging Regions highlights the nature and implications of regional inequalities in Europe and recommends how cohesion policy can be leveraged to maximize its impact on lagging regions, and on the businesses and people in these regions. The report has several key messages: regional inequalities are high and likely to rise; Europe’s lagging regions are going in opposite directions, but face common challenges; cohesion policy can maximize its impact on lagging regions by explicitly targeting regional potential and equality of opportunity rather than convergence; cohesion policy priorities can be rebalanced to help deliver on regional potential; and delivery of regional policy needs to engage ever more deeply at the ground level. This report aims to contribute to the debate on the future of cohesion policy, with a specific focus on lagging regions. It calls for a further shift in the objectives of cohesion policy towards an increasingly ‘region-centered’ approach that aims to maximize potential in all regions, while seeking convergence of opportunities for individuals, no matter where they live.